This will be proved using induction on
The base case, k
. k':
. (
f':(
(m-1)
k'). Inj(
(m-1);
k'; f'))
m-1
k'
The problem is then to show that k
m
k
m;
k; f)
Obviously, k
k-1
(m-1)
(k-1)
(m-1);
(k-1); f')
Such a construction is
Def Replace value k by f(m) in f == Replace values x s.t. x= k by f(m) in f
Def (Replace values x s.t. P(x) by y in f)(i) == if P(f(i)) y else f(i) fi
Thm* Inj( (m+1);
(k+1); f)
Inj(
m;
k; Replace value k by f(m) in f)
This last theorem is sufficient for concluding our argument.
QED
Note: | Considering ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() |
This is the key lemma to the proofs of the uniqueness of counting, and the pigeon-hole principle, i.e.,
Thm* (A ~ m)
(A ~
k)
m = k
Thm* m,k:
, f:(
m
k). k<m
(
x,y:
m. x
y & f(x) = f(y))
About:
![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() |
![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() |
![]() |